Implementasi RFID Berbasis Arduino untuk Meningkatkan Keamanan Inventaris di Laboratorium SMK - Ifan Fauzi Firmansyah (LKP Unity Academy, 2024)
This study aims to improve the security of laboratory inventory at SMKS Al Muhajirin by using RFID technology integrated with student cards as access keys. This system is designed to differentiate student cards of grades 11 and 12 to prevent loss or damage to laboratory equipment during learning activities. Through student training and system testing, the results showed a system accuracy rate of 90% in recognizing valid cards. From the results of the questionnaires collected, the majority of students stated that the use of RFID was easy and suitable for implementation in the laboratory. Further development is directed at improving system integration with the school database and expanding its application in other schools. This study makes a positive contribution to the security of school laboratory facilities, which can help smooth technology-based learning activities.